Effect of 45 full-scale WWTPs on tropical receiving water bodies in Brazil by partial least squares-discriminant analysis - Marina Salim Dantas; Fernando Jorge Corrêa Magalhães Filho; Cristiano Christofaro; Sílvia Corrêa Oliveira (Journal of Water, Sanitation and Hygiene for Development, 2022)
Treated wastewater may affect water quality and thereby significantly alter physicochemical and biological water quality parameters. The impact of wastewater treatment plants (WWTPs) on receiving water bodies is a multivariate problem. In this study, we investigated the effect of 45 full-scale WWTPs on tropical receiving water bodies in Mato Grosso do Sul State, Brazil. Most of the Pantanal wetland area lies within Mato Grosso do Sul State, thus representing a region of great hydrological relevance. Partial least squares-discriminant analysis (PLS-DA) was employed to discriminate samples collected at four WWTPs monitoring sites: influent, final effluent, upstream, and downstream of the discharges. The model demonstrated excellent accuracy when discriminating the influent from the effluent samples, but poor accuracy when discriminating upstream and downstream samples, indicating the high dilution capacity of the receiving water bodies as a critical factor in the water resources management. The results demonstrate the great potential of the methodology for better water resources management, which can be used in even more complex WWTP databases, allowing the assessment of effluent disposals' impacts in detail. It is recommended to use this methodology in water-limited regions to determine the effect of disposals in areas with different characteristics. HIGHLIGHTS Effluents from WWTPs may affect the water quality of receiving water bodies.; The impact of WWTPs on receiving water bodies is a multivariate problem.; The use of the PLS-DA technique allows a better water resources management and the determination of effects of WWTPs on receiving water bodies.; Classification models’ accuracy highlights the tropical Brazilian watercourses’ high dilution capacity.;